Cuba. Empresas y Economia : memorias del primer viaje de estudios de la Universidad de Puerto Rico, Facultad de Administracion de Empresas - Aponte García, Maribel (Clacso, 2016)
Co-edited by the College of Business Administration, University of Puerto Rico. In 2015, a group of Puerto Rican academics and students had the initiative to visit Cuba, an opportunity in which they received a series of conferences on a wide range of topics related to the Cuban reality. In Havana they had the support of the Chair of Caribbean Studies of the University of Havana. To this were added other institutions such as the "Raúl Roa García" Higher Institute of International Relations. It was a very positive experience for Puerto Ricans and Cubans. Fortunately, it was not left alone in interesting conferences and exchanges and diverse visits. Beyond the mutual enrichment that the direct contact between Puerto Ricans and Cubans –which allowed us to get to know each other better and verify, once again, how much in common there is between us– this interesting compilation of articles bequeaths us.